Synergistic effect of microneedle-delivered extracellular matrix compound and radiofrequency on rejuvenation of periorbital wrinkles - Cheng, Haiyan; Zhang, Ruina; Zhuo, Fenglin (Frontiers in Medicine, 2022)
Background: A combination of minimally invasive modalities can induce collagen regeneration more quickly and promote the penetration of topical agents, thus promoting skin rejuvenation. In the present study, we aimed to investigate the synergistic efficacy of extracellular matrix compound (ECM-C) via microneedle(MN) and radiofrequency (RF) on periorbital wrinkles. Method: A total of 25 participants with periorbital wrinkles were selected for this study. The left and right side of the periorbital area was randomly given ECM-C via MN or ECM-C via MN combined with RF. MN combined with ECM-C treatment was given 5 times at 2 weeks intervals, whereas RF treatment was given 3 times at 4-week intervals. Wrinkles by VISIA® system, biophysical parameters such as skin hydration, transepidermal water loss (TEWL), erythema index, melanin index by CK multiple probe adapter, and skin elasticity and skin thickness by DermaLab Combo® were assessed, and photos were taken at the baseline and 2 weeks after the last treatment. Subjective assessments, such as Crow’s Feet Grading Scale (CFGS) and Global Aesthetic International Scale (GAIS) satisfaction were also recorded. Result: A total of 25 participants with an average age of 43 participated in this trial. Periorbital wrinkles on both sides decreased after the treatment, and the side treated with ECM via MN and RF showed better improvement than the other side with ECM-C via MN alone. Skin hydration increased after the treatment on both sides. TEWL, skin erythema, and skin melanin indexes were not changed. Skin elasticity and skin thickness increased more on the side of ECM-C via MN and RF than on the other side of ECM-C via MN alone. The evaluation scores for CFGS improved on either side; however, no difference was found for CFGS and GAIS between intergroup comparison after the treatment. Conclusion: The objective assessment of wrinkles, elasticity, and thickness of periorbital skin improved more on the side with ECM-C treatment via MN combined with RF than on the other side of ECM-C treatment via MN only. However, no statistically significant difference was found between the subjective CFGS and GAIS evaluation of the two sides.